Evaluation of the influence of hydrodynamic cavitation treatment of dark petroleum products on the yield of fractions with boiling points up to 400°C - B. V. Peshnev; E. V. Burlyaeva; V. B. Terenteva; D. V. Nikishin; A. I. Nikolaev; K. S. Andronov (Тонкие химические технологии)
Objectives. The reduction of the anthropogenic burden on the environment is generally associated with the transition to alternative energy sources. However, some of these have only regional significance, while the effectiveness of others remains doubtful. On this point, innovative processes aimed at increasing the depth of oil refining may be equally important for reducing the carbon footprint. Wave-based technologies such as cavitation may also be included in these processes. Among the various methods for inducing such cavitation phenomena in oil refining, hydrodynamic approaches are especially promising. It has been shown that the treatment effectiveness increases with greater pressure or when augmenting the number of cavitation processing cycles. The aim of this work is to identify the factor (i.e., pressure gradient or number of treatment cycles) having the greatest influence on the change of the characteristics of the oil product.Methods. Cavitation phenomena were created by pumping dark oil products through a diffuser. The pressure gradient ranged from 20 to 50 MPa, while the number of cavitation processing cycles varied from 1 to 10. The influence of cavitation conditions on the change of fractional composition of petroleum products was analyzed. Target fractions are those having a boiling point up to 400°C.Results. It is shown that increased pressure generated in the diffuser leads to a linear increase in the yield of desired cuts. The dependence of the yield of these fractions on the number of processing cycles is described by the growth model with saturation. A proposed equation describes the influence of pressure and number of cycles on the yield of the fractions from initial boiling point temperature (TIBP) to 400°C following cavitation processing of dark oil products. Some of the coefficients of this equation have been associated with the physicochemical characteristics of the feedstock.Conclusions. An equation for predicting the maximum possible yield of the TJBP-400°C fraction as a result of cavitation processing under different conditions of the process is proposed according to the physicochemical characteristics of the feedstock. The prediction error did not exceed 12%. The equation analysis and comparison of energy consumption between different process regimes shows that a higher yield of the target product is achieved by increasing pressure gradient rather than the number of processing cycles.